System Information Management Sales of TB Prima Keloran Equipment and Goods with the Waterfall Method - Dwi Baskara, Yusril; Wibawa; Putri, Puji Handayani; Pratisto, Eko Harry (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2024)
In the digital era, many company switch to system information to improve efficiency and retrieval decision . However , Prima Keloran Building Store Still use method manual bookkeeping in management sales . This method face various weaknesses , such as risk error recording by employees , difficulties data access , and limitations in reporting as well as analysis sales . With growth business and increasing transaction volumes , the need will more system​ efficient become the more important . Implementation system information management sale with Waterfall method can become effective solution . This method follow step sequentially , starting from analysis need until implementation , so that allow developers to meet need specific shop in a way systematically . With system this , it is expected sales data management become more accurate and real-time, as well as analysis processes for planning strategic can made easier . Research This aims to design and implement capable system​ overcome constraint moment this and support development Prima Keloran Building Store business . With Thus , the implementation system This expected No only overcome existing problems , but also constructive ones a strong foundation for growth business in the future.